Why the UK's Fiscal Charter is Doomed to Fail: An Analysis of Austerity Economics during the First and Second Cameron Governments - Richard Murphy; Ronen Palan (City, University of London, City Political Economy Research Centre (CITYPERC), 2015)
The economic rationale for austerity policies harks back to a highly controversial proposals that originated in the 1990s known as 'expansionary fiscal contraction.' This paper explores these ideas relating to austerity and suggests that matters have not worked out as George Osborne expected. Furthermore, since the broad assumptions made by HM Treasury and the OBR remain the same in 2015 as they were in 2010, the paper presents an argument why austerity plans for the period 2016–2020 are also unlikely to succeed. The core arguments in the paper can be summarised by the following bullet points: Politically motivated suggestions that the economy crashed in 2007–08 because of Labour's overspending are not supported by the data. Indeed, by the time it left office the Labour government had adopted a more realistic basis for economic forecasting than the following government. In contrast to the generally perceived view, austerity only hit current spending per head from 2013 onwards, from which time on a significant downward trend in current spending per head of population is noticeable in the available data and forecasts. Despite the rhetoric of increasing and intolerable debt interest burden, the actual cost per head in 2015–16 is unlikely to be greater than pre-crisis levels on a per capita basis. The second Cameron government is planning to increase government spending, particularly in discretionary areas at around the time of the next general election in 2020. There has been a fundamental shift in the way that government spending benefits people in the UK. 'Feel good items' spending (health, education, infrastructure) per capita has declined sharply since 2008, while annually managed spending (mainly welfare and debt interest) has increased. These diverging trends clearly have differential effects on groups in society. Government policy aims to increase income tax and national insurance as a proportion of overall revenue, and at rates in excess of GDP growth, in the next five years, whilst reducing corporation taxes significantly. The government forecaster – the Office for Budget Responsibility (OBR) – is adopting a low, and in our view, unrealistic multiplier for government spending (range of 0.6 to 1.0). This is much lower than the one adopted by the IMF (0.9 to 1.7) or Standard & Poor (up to 2.5). The low multiplier adopted by the OBR has led to persistent overestimation of the benefit of austerity and constant upwards revision of public borrowing needs. The Office for Budget Responsibility forecasts for balancing the books by 2020 is premised on very significant, and in our view unrealistic, changes in the pattern of behaviour of the private sector within the UK economy and the external sectors over the next few years. The Fiscal Charter is neither feasible, nor desirable, for the UK economy. It is not desirable because it is premised on considerable growing debt burdens shouldered by the private sectors (households and business community) and overseas trade sector. It is not feasible because it assumes a linear and highly magnified projections of growth trends in the private and external sectors that began an either in the middle or 2014 or the early 2015 into the future but are very unlikely to continue unabated. If the rate of inaccuracy of OBR forecasts from 2011–12 to 2015–16 was replicated in the years 2015–16 to 2019–20 then, based on the July 2015 OBR forecast, an additional 162 billion would be borrowed over this period, and at the end of the 2015-2020 parliament the budget would not be running a surplus of 10.2 billion but would instead be showing a deficit of 39.3 billion
Keywords: 330